Lipids: new biology and therapeutic targets revealed through human genetics - Runz, Heiko (Clinical lipidology, 2013)
The Deuel Conference on Lipids, Napa Valley, CA, USA, 5-8 March 2013This year’s Deuel Conference on Lipids focused on the seminal contribution of human genetics to lipid biology and disease. Named in honor of Harry J Deuel Jr, famous single author of the three-volume textbook The Lipids (Interscience Publishers Inc., NY, USA) and established in 1955, the Deuel Conference is considered the longest-standing annual meeting on lipid metabolism in the USA. The 2013 meeting took place at the Silverado ResortofNapaValley(CA,USA)andwascharacterizedbyfirst-rankscientific contributionsanddiscussionsinafriendlyandinformalsetting.Fourscientificsessions over 2 and a half days, a poster session and generous breaks allowed for stimulating scientific,aswellassocialinteractionsofscientistsfromacademiaandindustryalike.
Published online: 18 Jan 2017
Gesehen am 07.02.2022